KEPADATAN POPULASI KUMBANG TANDUK (Oryctes rhinoceros L.) PADA TANAMAN KELAPA SAWIT DI PTPN VI UNIT USAHA OPHIR PASAMAN BARAT - -, Wesi - (Pendidikan Biologi, 2014)
Asiatic rhinoceros beetle ( Oryctes rhinoceros L. ) is an important pest in plantations of oil palm and coconut as the base of the plant canopy broaching . Based on this research has been conducted in order to determine the amount of the Horn Beetle Population Density on Plant Oil Palm in PTPN VI Ophir Pasaman West Business Unit .The study was conducted in February- March 2014 in PTPN VI Cambodgien Ophir IV Business Unit West Pasaman , using the descriptive survey method by means of direct collection of beetle horns of the research sites . Field sampling conducted during the first month on the location of the TBM and TM ie , one week in the light and one week in the dark by using pheromone traps containing ferotrap , preserved beetle horns obtained by using a solution of 70 % alcohol . Verification of beetle horns performed at the Laboratory of Zoology STKIP PGRI West Sumatra . Results calculated using the formula density , followed by t-test analysis at level Î± of 0.05% .From the results of research on the horn beetle population densities obtained a total population of beetle horns . was 250 ind/trap , and show characteristic horn beetle , dark brown body color , the horn section there is caput . At the end of the female abdomen are fine hairs , whereas in male hairless . Total body length of males and females ranged from 41- 43 mm , and the length of the horn ranges are 9-10 mm . Average density of beetle horns on the TBM and TM moon dark and bright moon was 33.5 ind / trap during bright moon and new moon .